Asthma mortality in Latin America - Neffen, Hugo; Baena Cagnani, Carlos E.; Malka, S.; Solé, Dirceu; Sepúlveda, R.; Caraballo, Luis R.; Caravajal, E.; Rodríguez Gavaldá, R.; González Díaz, Sandra Nora; Guggiari Chase, J.; Díez, C.; Baluga, J; et al. (International Association of Asthmology, 1997)
The Latin American Society of Allergy and Immunology coordinated this project to provide reliable data for gaining knowledge about our present situation, which is a condition indispensable to changing.